A Study on Myths and History of Indrathan, Dahachowk - Thapa, Sabita (Nepalese Culture, 2024)
Indradaha has its own cultural importance. There is a myth that "Indra", King of heaven during Satya Yuga came here and took bath. On every Bhadra Shukla Purnima Day, a day after Indra Jatra celebration in Basantapur, thousands of people visit this place for taking bath in this pond. Archaeology, the scientific study of the material remains of past human life and activities. Archaeological investigations are a principal source of knowledge of prehistoric, ancient, and extinct culture. In the Satyayuga, it is believed that King Indra of the heavens came and tied an elephant in a gold necklace and bathed in Indradaha. On the occasion of Indradaha bathing fair on the hill, it is considered to be a wonderful feature to fill Indradaha completely. This place has its own value including different myths and settled pattern of local people from the ancient era. To explore more about the Indrathan, the most famous deities were stablished i.e. Indra, Indrayani, Basuki, and other idols next to the Indra place are privileged to worship Ganesha, Surya, Durga, Bhairav, Garuda, and Saligram etc. another important aspect of explore this place is mythological significance is found in the Nepal Mahatma of chapter 185 under the snowy section of the skanda purana Most of the local people says about indrathan is related with indrajatra which is held in Kathmandu valley and another myth about kalu panday.